Fuzzy logic direct torque control of induction motor for photovoltaic water pumping system - Aicha Belgacem; Yahia Miloud; Mohamed Mostefai; Fatima Belgacem (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This study presents a fuzzy logic direct torque control for induction motor to be used in photovoltaic (PV) water pumping system. The system is intended to be less expensive and simple while maximizing PV array power utilization. For this purpose, a smart technology based on fuzzy logic controller (FLC) has been implemented to track the maximum power which has been successfully used in solar water pumping systems under different irradiance levels. Next, to alleviate the disadvantages of standard DTC, we chose fuzzy direct torque control (FDTC) for induction motors driving a centrifugal pump. Furthermore, this study includes the usage of IP with antiwindup and slide mode speed controller (SMC) instead of the traditional proportional-integral speed controller. Finally, the induction motor (IM) speed has been optimized with an optimum speed control in order to maximize the pump’s hydraulic parameters. The FDTC, with its SMC outperforms the photovoltaic pumping system (PVPS) in terms of dynamic performance and robustness. To develop a full simulation model of the proposed PVPS configuration under various climate conditions, MATLAB environment and associated Simulink are used.